A Viable Rehabilitation Approach with Maxillary Cast Partial Denture and Mandibular Over Denture - A Case Report - Pradhan, Bismita; Joshi, S P; Verma, A (Journal of Nepalese Prosthodontic Society, 2019)
Prosthodontic rehabilitation is indicated to restore function, esthetics and phonetics. The prosthetic options for rehabilitation of partial edentulism include removable partial dentures (RPD), over dentures, and implant supported prosthesis. Any tooth replacement should be performed by a detailed evaluation of the existing dental situation and functional condition of the patient. Besides, the risks, benefits and costs of the selected treatment modality should be discussed with the patient. Choice of prosthetic treatment modality is mainly determined by the patient’s needs and expectations, social and economic aspects, educational level, as well as the general health status, oral functional benefits, esthetics, prognosis of the remaining teeth and patient motivation to maintain oral hygiene. This clinical report describes rehabilitation of a partially edentulous patient with maxillary cast partial denture (CPD) and mandibular tooth supported over denture.